Extrinsic factors influencing the bid/no-bid decision of construction contracting firms: Impact of firm size and experience - Maqsoom, Ahsen; Ashraf, Hassan; Choudhry, Rafiq Muhammad; Khan, Sufian Younas; Dawood, Muhammad; Tariq, Adeel (Revista de la Construcción. Journal of Construction, 2020)
Construction contracting firms (CCFs) are functioning in a highly volatile and competitive industrial environment making it imperative to bid for the projects that can produce the most return and market share. The decision making process to bid or not is based on various factors that vary from project to project and firm to firm. The aim of this work is to analyze the impact of firm size and experience on extrinsic factors influencing the bid/no-bid decision for construction projects. The questionnaire was pilot tested and designed in three parts. The final questionnaire was sent to 300 CCFs registered with Pakistan Engineering Council (PEC) and respondents were asked to rate the factors on a Likert scale. Out of 300 questionnaires, 167 completed responses are returned representing a response rate of 56%. The collected data are then analyzed using Mann-Whitney U test through Statistical Package for Social Sciences (SPSS). Findings show the various degrees of differences between small and large, and young and mature CCFs with regard to factors influencing the bid/no-bid decision. Small firms need to overcome increasing market value and number of competitors in the market. They need to develop relationship with government officials in order to secure their bids. Mature firms need to review the payment practices of clients, politician pressure and business level of the client before entering into the bid. Availability of required material and skilled labor are of prime importance for the mature firms’ success.